Analisis Dampak Strategi Promosi Dan Penetapan Harga Di Shopee Terhadap Tingkat Kepuasan Konsumen Produk Konilife Pada PT. Konimex Cabang Tangerang - Firna Khairunisa; Asep Sulaeman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This study aims to analyze the influence of promotional strategies and pricing on customer satisfaction with Konilife products on the Shopee platform. The background of this study is based on the increasingly intense competition in the e-commerce industry, which encourages companies to implement effective marketing strategies to improve customer satisfaction. This study employed a qualitative approach, with data collected through questionnaires distributed to consumers who had purchased Konilife products via Shopee. The collected data were analyzed to determine the influence of promotional strategies and pricing on customer satisfaction. The results indicate that promotional strategies have a positive effect on customer satisfaction. Promotional activities carried out through Shopee, such as advertisements, discounts, and the provision of clear and attractive product information, were able to increase consumers' purchase intentions and assist them in making purchasing decisions. In addition, pricing also had a positive influence on customer satisfaction. Most consumers perceived the prices of Konilife products as affordable and proportional to the quality received, thereby creating a positive value perception and increasing post-purchase satisfaction. However, some consumers perceived the prices differently when comparing Konilife products with similar competing brands. Overall, effective promotional strategies and appropriate pricing were proven to enhance customer satisfaction with Konilife products on Shopee. The SWOT analysis produced Strength, Weakness, Opportunity, and Threat scores of 4.40, 3.50, 4.45, and 4.10, respectively, resulting in SWOT coordinates of (0.90, 0.35), which place the company in Quadrant I (Growth Strategy). Furthermore, the Quantitative Strategic Planning Matrix (QSPM) analysis showed that Strategy 1 (Shopee Promotion Optimization) achieved the highest Total Attractiveness Score (TAS) of 15.55, compared to 15.25 for Strategy 3 and 14.90 for Strategy 2. These findings indicate that optimizing digital promotional activities through Shopee features is the most effective strategy for improving customer satisfaction with Konilife products at PT Konimex Tangerang Branch. The results of this study are expected to provide valuable insights and serve as a reference for the company in developing more effective and customer-oriented marketing strategies.